Basic human values and political participation on the internet: Different basic motives for male and female groups - Indro Adinugroho; Maya Trisyanti (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2021)
Even though participation through the internet has been popular in Indonesia, gender inequality between males and females often affecting the degree of participation. Thereby, identification of basic values that may contribute toward PPI is fundamental to be examined. This study aims to examine the correlation between political participation on the internet and basic values as the predictor in two gender groups, male and female. The result of this study revealed that males and females have different motives for participating in politics through the internet. Female tends to utilize their basic values to support their passive participation while the male is concentrated more on active participation. In conclusion, different basic values as psychological motives in PPI convey different meanings of politics in females and males that should be addressed through different actions.